Left atrial appendage occlusion combined with cryoballoon or radiofrequency ablation: One-year follow-up comparison - Ma, Yibo; Guo, Lanyan; Hu, Miaoyang; Yan, Qun; Liu, Haitao; Yi, Fu (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background: A one-stop procedure involving catheter ablation and left atrial appendage occlusion (LAAO) is an option for high-risk atrial fibrillation patients. Few studies have reported the efficacy and safety of cryoballoon ablation (CBA) combined with LAAO, and no studies have compared the combination of LAAO with CBA or radiofrequency ablation (RFA). Methods: A total of 112 patients were enrolled in the present study; 45 patients received CBA combined with LAAO (group 1), and 67 patients received RFA combined with LAAO (group 2). Patient follow-up was performed for 1 year to detect peri-device leaks (PDLs) and safety outcomes (defined as a composite of peri-procedural and follow-up adverse events). Results: The number of PDLs at the median 59 days follow-up was comparable between the two groups (33.3% in group 1 vs. 37.3% in group 2, p = 0.693). Safety outcomes were also comparable between the two groups (6.7% in group 1 vs. 7.5% in group 2, p = 1.000). Multivariable regression showed that PDLs risk and safety outcomes were all similar between the two groups. Subgroup analysis of PDLs indicated no significant differences. Follow-up safety outcomes were related to anticoagulant medication, and patients without PDLs were more likely to discontinue antithrombotic therapy. The total procedure and ablation times were all significantly shorter for group 1. Conclusion: When compared with left atrial appendage occlusion combined with radiofrequency, left atrial appendage occlusion combined with cryoballoon ablation has the same risk of peri-device leaks and safety outcomes, but the procedure time was significantly reduced.